Taken Out of Context: Defending Civic Education From the Situationist Critique - Ben-Porath, Sigal; Dishon, Gideon (Philosophical Inquiry in Education, 2015)
Situationists have suggested that educational efforts to improve character and instill virtues should be abandoned, as individuals’ behavior is predicted by contexts and situations rather than by character traits. More recently it has been suggested that civic education and especially the effort to cultivate civic virtues are ineffective for similar reasons and should be replaced by the introduction of desirable social norms and institutions. After surveying the debate on this topic in the first part of the essay, we suggest that in fact virtues should not be judged as existing within one person and absent from another based on their behavior in a single instance. Rather, virtues should be understood as composite and probabilistic and therefore strengthening them is a valuable endeavor. In considering civic virtues specifically we argue that the social and public nature of their expression make schools excellent contexts for cultivating and practicing democratic civic virtues. Even the best institutional structures of a well-functioning democratic society rely on the compliance of virtuous citizens, and the situationist preference for desirable social norms is implicitly predicated on virtuous citizens to institute and follow those norms. Moreover, civic education in a democracy strives to cultivate more than compliance with norms of conduct. It aspires to nurture youth who see themselves as responsible to, and capable of shaping the norms of the society in which they live. We thus incorporate some of the insights from situationism into a revamped view of civic education.